Preparation method of modified hydrothermal carbon material for hexavalent chromium adsorption
By doping zero-valent iron into hydrothermal carbon materials and adopting one-step hydrothermal reaction and alternating washing technology, the problem of insufficient adsorption performance of hexavalent chromium is solved, and efficient hexavalent chromium adsorption and reduction effects are achieved, which is suitable for industrial-scale production .
Patent Information
- Application Number
- CN202411099545.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art cannot effectively remove hexavalent chromium pollutants, and the stability and contact efficiency of hydrothermal carbon materials during adsorption are insufficient, making it difficult to meet the needs of industrial-scale production.
Iron-doped mesoporous carbon materials are prepared by doping zero-valent iron into hydrothermal carbon materials, using a one-step hydrothermal reaction, combining alternating washing and freeze-drying techniques to improve the adsorption performance and stability of the material, and through stirring uniformity and The hydrophilicity of iron ions enhances adsorption effect.
It achieves efficient hexavalent chromium adsorption and reduction performance, improves the stability and contact efficiency of the material, reduces cost and processing time, and enhances the removal rate and purity of pollutants.
Smart Images

Figure CN119186491A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modification and preparation of iron-doped hydrothermal carbon materials, and in particular to a method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption. Background Art
[0002] Hexavalent chromium (Cr(VI)) is a common water pollutant, and its presence poses a serious threat to human health and the environment. Hexavalent chromium pollution usually comes from industrial wastewater, electroplating wastewater, leather manufacturing, steel production, and waste dumps. It not only harms the aquatic ecosystem, but also may cause serious health problems such as cancer and skin inflammation. Therefore, it is crucial to find efficient, environmentally friendly and economically feasible methods to remove Cr(VI) pollutants from water.
[0003] Hydrothermal carbon is a new type of adsorption material with the characteristics of simple preparation process, strong adsorption capacity, thermal stability and chemical stability. It has attracted much attention in the field of heavy metal adsorption and separation in the process of water body remediation. A single hydrothermal carbon material sometimes cannot fully meet the special requirements in the field of adsorption, so it is often necessary to modify it to improve the adsorption effect. Zero-valent iron has reducing properties and can reduce the highly toxic hexavalent chromium to non-toxic and stable trivalent chromium ions, but zero-valent iron is easy to agglomerate. Loading zero-valent iron on hydrothermal carbon can improve its stability. Compared with other porous carbon materials, the preparation of hydrothermal carbon materials does not require a special alkaline activation process. The preparation process is simple, the cost is low, and the stability is strong. It is suitable for large-scale industrial production. Hydrothermal carbon materials also have the characteristics of hydrophilic outer shell and hydrophobic inner shell. It can prevent the modified iron from falling off while increasing the contact with pollutants, and has a high adsorption and removal efficiency. Summary of the invention
[0004] Technical issues solved:
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption, which has excellent Cr(VI) adsorption and reduction performance advantages and solves the above technical problems.
[0006] Technical solution:
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption, the specific steps are:
[0008] Step 1: Prepare hydrothermal carbon, dissolve 19.8 grams of glucose in 200 milliliters of pure water, stir evenly and place in a hydrothermal reactor, react at a constant temperature of 180°C-200°C for 5 hours, wash the product with pure water and ethanol alternately and freeze-dry to obtain a black hydrothermal carbon solid product;
[0009] Step 2: Preparation of iron solution: 0.5 g of polyethylene glycol and 1.946 g of ferrous sulfate heptahydrate were dissolved in a solution of 100 ml of ethanol and water to prepare a 0.07 M iron solution;
[0010] Step 3: Preparation of iron-modified hydrothermal carbon: 4 g of hydrothermal carbon solid product was mixed with 0.07 M iron solution and stirred evenly, 50 ml of 1 M potassium borohydride reducing agent was dripped into the mixed solution at a rate of 2 ml / min, and the mixed solution was continuously stirred;
[0011] Step 4: Filtration and washing: the mixed solution is filtered with a 0.45 μm filter membrane, and then washed alternately with pure water and ethanol and freeze-dried to obtain a modified hydrothermal carbon material product.
[0012] Preferably, when the isothermal reaction temperature in step 1 is 200° C., the pH value of the corresponding hexavalent chromium solution is 1.65-3.0.
[0013] Preferably, when the isothermal reaction temperature in step 1 is 180° C., the pH value of the hexavalent chromium solution is 3.0-6.0.
[0014] Preferably, the product after the reaction in step 1 is washed alternately with pure water and ethanol, wherein the pure water accounts for 2-3 times the volume of the product, the ethanol accounts for 1-2 times the volume of the product, and the total number of washing times is 2-4 times.
[0015] Preferably, the freeze-drying freezing temperature in step 1 is -40°C to -60°C, and the drying time is 24 hours.
[0016] Preferably, the mixing ratio of the solution of ethanol and water in step 2 is 3:7.
[0017] Preferably, the step of preparing the iron solution in step 2 is:
[0018] S1.1. Dissolve ferrous sulfate heptahydrate: Place the weighed ferrous sulfate heptahydrate into a container, add 30-50 ml of distilled water, and stir to completely dissolve it;
[0019] S1.2, adding polyethylene glycol: adding 0.5 g of polyethylene glycol to the dissolved ferrous sulfate heptahydrate solution, and continuing to stir until the polyethylene glycol is completely dissolved;
[0020] S1.3, dilute to total capacity: transfer the above solution to a 100 ml measuring cylinder or flask and dilute the volume of the solution to 100 ml with distilled water;
[0021] S1.4. Mix evenly: Shake or stir with a glass rod to mix the polyethylene glycol and ferrous sulfate heptahydrate solution evenly.
[0022] Preferably, in the step 3, 4 g of the hydrothermal carbon solid product is mixed with 0.07 M of the iron solution and stirred evenly for 3 min to 5 min, and the stirring speed is 50 rpm.
[0023] Preferably, the mixed solution is continuously stirred at a speed of 30 rpm.
[0024] Preferably, in the step 4, when pure water and ethanol are washed alternately, the proportion of pure water is 2-3 times the volume of the mixed solution, and the proportion of ethanol is 1-2 times the volume of the product mixed solution.
[0025] Compared with the prior art, the present invention provides a method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption, which has the following beneficial effects:
[0026] 1. The present invention uses hydrothermal carbon as a carrier for preparing iron-doped mesoporous carbon materials, and iron doping is completed simultaneously during the preparation process. The original hydrothermal carbon carrier can be prepared through a one-step hydrothermal reaction. The iron-doped mesoporous carbon material generated by iron doping has a higher iron content, achieving the beneficial effect of excellent Cr(VI) adsorption and reduction properties.
[0027] 2. The present invention uses pure water and ethanol alternately for washing in a certain proportion, which can more effectively remove impurities, improve the purity of the product, and reduce subsequent processing costs and time. Freeze drying can optimize the water removal efficiency and reduce the risk of damage to heat-sensitive materials, thereby improving the quality and use efficiency of the product. In step 2, ferrous sulfate heptahydrate and polyethylene glycol are directly used to prepare the iron solution, which simplifies the operation process, saves time and labor costs, and ensures uniform mixing by clarifying the stirring time and speed, thereby improving the efficiency of the reaction, reducing the waste of materials, ensuring sufficient reaction, and reducing the loss of unreacted components, thereby achieving the beneficial effects of lower preparation cost and higher efficiency.
[0028] 3. The present invention ensures uniform mixing of the hydrothermal carbon material and the iron ions through accurate stirring conditions, thereby increasing the contact area between the two and enhancing the adsorption capacity of pollutants. The porous structure of the solid product of the hydrothermal carbon material provides a large number of adsorption sites, which can effectively capture pollutants such as hexavalent chromium and increase the adsorption efficiency. The iron ions, as modifiers, can not only increase the hydrophilicity of the hydrothermal carbon material, but also form chemical bonds with the pollutants, thereby improving the adsorption capacity. The iron ions, as catalysts, enhance the removal rate of pollutants. The combination of iron ions and hydrothermal carbon materials is designed with strength and stability in mind. The hydrophilic outer layer and hydrophobic inner layer of the iron-doped hydrothermal carbon enhance the modification effect and reduce the problem of separation in the aqueous phase, thereby achieving the beneficial effect of being able to better contact with the pollutants for adsorption and removal and reducing the risk of falling off of the iron ions added by the modified inner layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a process flow chart of a method for preparing an iron-doped hydrothermal carbon material according to Example 1 of the present invention;
[0030] Figure 2 The scanning electron microscope image-energy dispersive X-ray spectrum of the iron-doped hydrothermal carbon material of Example 1 of the present invention;
[0031] Figure 3 This is an energy spectrum diagram of the iron-doped hydrothermal carbon material according to Example 1 of the present invention;
[0032] Figure 4 A nitrogen adsorption-desorption isotherm diagram of the iron-doped hydrothermal carbon material of Example 1 of the present invention;
[0033] Figure 5 This is a scanning electron microscope image of the iron-doped hydrothermal carbon material of Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] See also Figure 1-5 , a method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption, comprising the following specific steps:
[0037] (1) Preparation of hydrothermal carbon: 19.8 g of glucose was dissolved in 200 ml of pure water, stirred evenly and placed in a hydrothermal reactor, and reacted at a constant temperature of 180° C. to 200° C. for 5 hours. The reaction product was washed alternately with pure water and ethanol and freeze-dried to obtain black hydrothermal carbon solid products, namely HTC-180 and HTC-200;
[0038] (2) Preparation of iron solution: 0.5 g polyethylene glycol (HO(CH 2 CH 2 O) n H) and 1.946 g of ferrous sulfate heptahydrate (FeSO 4 .7H 2 O) was dissolved in 100 ml of ethanol / water (V 乙醇 / V 水 =3 / 7) solution to prepare a 0.07M iron solution;
[0039] (3) Preparation of iron-modified hydrothermal carbon: 4 g of hydrothermal carbon solid product was mixed with 0.07 M iron solution and stirred evenly, 50 ml of 1 M potassium borohydride reducing agent was dripped into the mixed solution at a rate of 2 ml / min, and the mixed solution was continuously stirred;
[0040] (4) Filtration and washing: the mixed solution was filtered with a 0.45 μm filter membrane, and then washed alternately with pure water and ethanol and freeze-dried to obtain Figure 1 The modified hydrothermal carbon material product shown is obtained by grouping HTC-180 and HTC-200 and performing the process simultaneously to obtain Fe0-HTC-180 and Fe0-HTC-200.
[0041] like Figure 2 , Figure 3 The figure shows the scanning electron microscope image, energy dispersive X-ray spectrum and energy spectrum of the mesoporous carbon material loaded with zero-valent iron prepared in Example 1 of the present invention. It can be seen from the figure that the zero-valent iron has been successfully loaded on the mesoporous carbon; Figure 4 This is a nitrogen adsorption and desorption diagram of the zero-valent iron loaded mesoporous carbon material prepared in Example 1 of the present invention. It can be seen from the figure that the nitrogen adsorption and desorption curve of the material is a type IV curve, indicating that the prepared zero-valent iron loaded mesoporous carbon material is a typical mesoporous material.
[0042] Embodiment 2:
[0043] The two hydrothermal carbon solid products HTC-180 and HTC-200 prepared in Example 1 and the two modified hydrothermal carbon solid products Fe0-HTC-180 and Fe0-HTC-200 were added to four groups of hexavalent chromium solutions with a volume of 100 ml, respectively, and the adsorption capacity of hexavalent chromium by hydrothermal carbon at different pH values was measured. The measurement results are shown in Table 1.
[0044] Table 1 below shows the results of elemental analysis characterization of the hydrothermal carbon materials prepared at different hydrothermal temperatures and Fe addition modifications.
[0045] Table 1 Elemental analysis table of mesoporous carbon obtained under different hydrothermal temperatures and Fe addition modification
[0046]
[0047] As can be seen from Table 1, only 10%-15% of iron was added to the hydrothermal carbon.
[0048] Experimental Example 1:
[0049] The two hydrothermal carbon solid products HTC-180 and HTC-200 prepared in Example 1 and the two modified hydrothermal carbon solid products Fe0-HTC-180 and Fe0-HTC-200 were added to four groups of hexavalent chromium solutions with a volume of 20 ml, respectively, and the adsorption capacity of hexavalent chromium by hydrothermal carbon at different pH values was measured. The measurement results are shown in Table 2.
[0050] Table 2: Changes in adsorption capacity of hexavalent chromium by hydrothermal carbon at different pH values
[0051] name 2 Adsorption rate 4 Adsorption rate 6 Adsorption rate HTC-180(mg / L) 8.6 43% 3.9 19.50% 2.3 11.50% HTC-200(mg / L) 9.2 46% 6.2 31% 3.2 16% Fe0-HTC-18(mg / L) 18.16 90.8%% 17.02 85.1% 14.76 73.8% Fe0-HTC-20(mg / L) 19.75 98.80% 18.72 93.6% 16.58 82.9%
[0052] The results show that the adsorption capacity of the hydrothermal carbon material modified by Fe addition is better than that of the hydrothermal carbon material without Fe addition. The adsorption performance of Fe0-HTC-200 material is better than that of HTC-180 material; the hydrothermal carbon material modified by Fe addition has a higher ability to adsorb hexavalent chromium under acidic pH conditions.
[0053] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption, characterized in that: The specific steps are: Step 1: Prepare hydrothermal carbon, dissolve 19.8 grams of glucose in 200 milliliters of pure water, stir evenly and place in a hydrothermal reactor, react at a constant temperature of 180°C-200°C for 5 hours, wash the product with pure water and ethanol alternately and freeze-dry to obtain a black hydrothermal carbon solid product; Step 2: Preparation of iron solution: 0.5 g of polyethylene glycol and 1.946 g of ferrous sulfate heptahydrate were dissolved in a solution of 100 ml of ethanol and water to prepare a 0.07 M iron solution; Step 3: Preparation of iron-modified hydrothermal carbon: 4 g of hydrothermal carbon solid product was mixed with 0.07 M iron solution and stirred evenly, 50 ml of 1 M potassium borohydride reducing agent was dripped into the mixed solution at a rate of 2 ml / min, and the mixed solution was continuously stirred; Step 4: Filtration and washing: the mixed solution is filtered with a 0.45 μm filter membrane, and then washed alternately with pure water and ethanol and freeze-dried to obtain a modified hydrothermal carbon material product.
2. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 1, characterized in that: When the isothermal reaction temperature in the step 1 is 200° C., the pH value of the corresponding hexavalent chromium solution is 1.65-3.
0.
3. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 1, characterized in that: When the isothermal reaction temperature in the step 1 is 180° C., the pH value of the hexavalent chromium solution is 3.0-6.
0.
4. A method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 2 or 3, characterized in that: The product after the reaction in step 1 is washed alternately with pure water and ethanol, wherein the pure water accounts for 2-3 times the volume of the product, the ethanol accounts for 1-2 times the volume of the product, and the total number of washings is 2-4 times.
5. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 4, characterized in that: The freeze drying temperature in step 1 is -40°C to -60°C, and the drying time is 24 hours.
6. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 5, characterized in that: The mixing ratio of the solution of ethanol and water in step 2 is 3:
7.
7. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 1, characterized in that: The steps for preparing the iron solution in step 2 are as follows: S1.
1. Dissolve ferrous sulfate heptahydrate: Place the weighed ferrous sulfate heptahydrate into a container, add 30-50 ml of distilled water, and stir to completely dissolve it; S1.2, adding polyethylene glycol: adding 0.5 g of polyethylene glycol to the dissolved ferrous sulfate heptahydrate solution, and continuing to stir until the polyethylene glycol is completely dissolved; S1.3, dilute to total capacity: transfer the above solution to a 100 ml measuring cylinder or flask and dilute the volume of the solution to 100 ml with distilled water; S1.
4. Mix evenly: Shake or stir with a glass rod to mix the polyethylene glycol and ferrous sulfate heptahydrate solution evenly.
8. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 1, characterized in that: In the step 3, 4 g of the hydrothermal carbon solid product is mixed with 0.07 M of the iron solution and stirred evenly for 3 min to 5 min at a stirring speed of 50 rpm.
9. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 1, characterized in that: The mixed solution was continuously stirred at a speed of 30 rpm.
10. The method for preparing a modified hydrothermal carbon material for hexavalent chromium adsorption according to claim 1, characterized in that: In the step 4, when pure water and ethanol are washed alternately, the proportion of pure water is 2-3 times the volume of the mixed solution, and the proportion of ethanol is 1-2 times the volume of the product mixed solution.
